Designing modern Germany - Aynsley, Jeremy (London : Reaktion Books, 2009)
An account of the extraordinarily rich and complex history of German design since 1870. Jeremy Aynsley introduces key figures and offers analyses of their work across a range of media: graphics, interiors, industrial and furniture design, crafts, fashion and architecture.
Design ideals, design reform, design professions, 1870-1914 -- Experiment and tradition in design, 1917-33 -- Politics and design: reaction and consolidation, 1933-45 -- Reconstruction and the tale of two Germanys, 1945-75 -- Reunification: design in a global context, 1975-2005.
Includes bibliographical references and index.
Keywords: Design -- Germany -- History -- 20th century; Design -- Allemagne -- Histoire -- 20e siècle.; Design; Deutschland; Electronic books